Surveying Dentists' Perceptions of Caregiver Refusal of Topical Fluoride - Chi, D L; Basson, A A (JDR clinical and translational research, 2018)
The objective of this study was to assess dentists' perceptions of caregiver topical fluoride refusal behaviors. We administered an 8-item survey in 2015 and 2016 ( N = 582) and asked dentists about the extent to which fluoride refusal is a problem, refusal trends, comfort talking to caregivers who refuse, and perceived reasons why caregivers refuse. To examine geographic variation, we ran χ tests between dentists' location (US West vs. non-West) and the first 3 perception measures (α = 0.05). Nearly 80% of dentists believed fluoride refusal was a problem, and 42.3% believed it was a growing problem. A significantly larger proportion of dentists who saw fluoride refusal as a problem also believed refusal was a growing problem compared to those who thought refusal was not a problem (89.6% and 41.2%, respectively; P < 0.0001). Caregiver characteristics perceived to be associated with fluoride refusal included immunization refusal (41.3%), White race (37.6%), and high income (33.7%). Thirty-seven percent of surveyed dentists were uncomfortable talking to caregivers who refused. There were no geographic differences in perceptions of fluoride refusal as a problem ( P = 0.52). A significantly larger proportion of non-West dentists believed fluoride refusal has gotten worse (non-West: 65.5%, West: 41.2%; P < 0.0001), but more dentists from the West were uncomfortable talking to caregivers who refused (West: 86%, non-West: 67.4%; P < 0.0001). Caregiver refusal of topical fluoride may be a growing problem, and many dentists are uncomfortable talking to caregivers who refuse. Additional interdisciplinary research is needed to identify the reasons why caregivers refuse fluoride, which is an important next step in developing chairside interventions that address fluoride refusal behaviors. Knowledge Transfer Statement: The results of this study can be used by researchers to develop chairside strategies to help dentists identify and manage fluoride refusal behaviors in clinical settings. This could help preserve topical fluoride as an evidence-based preventive therapy and address a growing public health problem.